Self-esteem, self-control, and life satisfaction among amateur boxers - Chen, X.; Qiu, N.; Chen, C.; Wang, D. (Archives of Budo, 2020)
Background and Study Aim: Life satisfaction refers to a stable and generalized cognitive evaluation of an individual's overall living conditions or major aspects of life, and is an important indicator for measuring the quality of personal life and an indicator of subjective well-being. The purposes of the present study is knowledge about two issues: first, the relationship between self-esteem, self-control and life satisfaction; second, whether self-control mediates the relationship between self-esteem and life satisfaction.